COMBATING CORRUPTION BASED ON INTERNATIONAL RULES - Maskun, Maskun (Indonesia Law Review, 2014)
Corruption is a universal problem that is taking place all over the world, either in developed countries or developing or under developing countries. It is caused by some issues such as poorly designed economic policies, low levels of education, underdeveloped civil society, and the weak accountability of public institution. Those causes of corruption can be separated in some different types of corruption. The types are bureaucratic corruption, political corruption, grand corruption, and common corruption. In terms of tackling some problems of corruption, there are so many things to do including international law commitment. Some international law commitment can be seen like OAS Convention, OECD’s anti-bribery Convention, the UN Convention against Transnational Organized Crime, and the United Nation Convention against Corruption (UNCAC). Those laws must be analyzed not only in context of substantive of those laws but also how they are implemented in state practices.